Method and apparatus for treating discharge gas containing target gas in plasma state - JANG YUN-SANG; PAEK KWANG-HYON; JU WON-TAE (2021)
The present invention relates to a method and apparatus for treating a discharge gas containing a target gas in a plasma state, the method comprising the steps of: generating a plasma in a conversion region in which the conversion of the target gas occurs; supplying, to the conversion region, a conversion promoting agent containing a conversion promoting element of which the first ionization energy is not greater than 10eV for promoting the conversion of the target gas; supplying, to the conversion region, a conversion agent that produces conversion products by combining with the dissociation products of the target gas and prevents the dissociation products from recombining into the target gas; and supplying the exhaust gas containing the target gas to the conversion region. The method increases the conversion rate of the target gas contained in the exhaust gas and reduces the energy consumption required in the process. 本发明提供一种在等离子体相处理含有目标气体的排放气体的方法和实现其的装置，包括如下步骤：在进行目标气体的转化的转化区域生成等离子体；第一电离能作为低于10eV的元素，将含有促进目标